Hijrah as Multidimensional Renewal: Cross-Sectarian Tafsir Analysis of Quraish Shihab and Nāṣīr Makārim Shīrāzī - Kerwanto Kerwanto; Mujiburrohman Mujiburrohman; Mowafg Masuwd (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study explores the multidimensional concept of hijrah in the Qur’an through the perspectives of two contemporary exegetes representing the Sunni and Shia traditions: Muhammad Quraish Shihab (Tafsir al-Mishbah) and Nāṣīr Makārim Shīrāzī (Tafsir al-Amṯāl). Employing a qualitative library-based approach and a cross-mazhab thematic tafsir method, the research aims to uncover how both scholars interpret hijrah as a relevant social and spiritual transformation. Findings indicate that both exegetes view hijrah holistically, encompassing physical movement, social struggle, and inner purification. Shihab emphasizes hijrah as moral and societal renewal toward an inclusive and ethical community in the Indonesian context, while Shīrāzī highlights its spiritual dimension as an inner jihad against egoism and injustice. Despite doctrinal differences, both use similar analytical and literary-social methods, demonstrating a convergence on hijrah as a timeless call for ethical transformation and social justice. This cross-mazhab approach enriches Qur’anic scholarship by bridging sectarian perspectives and offering practical implications for contemporary Muslim societies.